Perceived Roles of Information and Communication Technologies in the Implementation of Continuous Assessment in Nigerian Secondary Schools - Olugbenga Gabriel Akindoju; Sunday Olaniyi Banjoko; Akinola Saliu Jimoh (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2011)
The study examined the roles of information and communication technologies (ICTs) in the conduct of continuous assessment in secondary schools in Lagos State, Nigeria. Adopting a survey type of descriptive research, a self developed questionnaire was administered on 240 respondents (principals, vice-principals and teachers) from 20 randomly selected secondary schools across 5 local government areas. Data collected was analyzed using descriptive and t-test inferential statistics at 0.05 level of significance, to answer the research questions, and test hypotheses respectively. Based on the analysis conducted, it was found that; both school managers and teachers are aware of the use of ICT for continuous assessment in secondary schools; schools do not have adequate resources for employing ICT for continuous assessment in schools;  there is no significant gender difference in teachers' awareness level on the use of ICTs for continuous assessment contrary to that of the school managers. Appropriate recommendations were made by the authors.